Literacy and Financial Management Effectiveness: The Mediating Role of Knowledge Management in Hospitals - Rury Prahistha Monali; Yuliansyah Yuliansyah; Chara P Tidespania Tubarad (Goodwood Publishing, 2026)
Purpose: This study examines the effects of employee motivation and financial literacy on financial management effectiveness, with knowledge management as a mediating variable. Research Methodology: This study was conducted in hospitals in Bandar Lampung, Indonesia. A quantitative explanatory design was employed. Data were collected using a structured questionnaire distributed to employees involved in financial and administrative activities through purposive sampling. The analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to test both direct and mediating relationships. Results: Employee motivation and financial literacy positively and significantly affect financial management effectiveness. Both variables significantly influenced knowledge management. Furthermore, knowledge management positively and significantly affects financial management effectiveness and mediates the relationship between employee motivation, financial management effectiveness, and financial literacy. Conclusions: The study concludes that Improving financial management effectiveness in hospitals requires enhancing employee motivation and financial literacy and strengthening knowledge management practices to support knowledge sharing, utilization, and organizational learning. Limitations: This study was limited to hospitals in Bandar Lampung and applied a cross-sectional design, which may limit the generalizability of the findings and the ability to infer causal relationships. Contributions: This study contributes to the literature by integrating employee motivation, financial literacy, and knowledge management into a unified model of financial management effectiveness in the healthcare industry. In practice, the findings provide insights for hospital management in designing strategies to improve human resource capabilities, strengthen financial literacy, and develop effective knowledge management systems.